2015
DOI: 10.17219/acem/40469
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Onlay Buccal Mucosal Graft Urethroplasty in the Treatment of Urethral Strictures – Does the Stricture Length Affect Success?

Abstract: Background. Treatment of urethral strictures can be challenging, but, with appropriate preoperative evaluation and surgical planning it is possible to achieve successful results. Objectives. To analyze if the stricture length affects the success with dorsal onlay buccal mucosal graft urethroplasty technique. Material and Methods. Between January 2004 and June 2010 a total of 40 patients with anterior urethral stricture were treated with dorsal onlay buccal mucosal graft urethroplasty. Age, etiology of the stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
9
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
11
9
3
Order By: Relevance
“…A recent meta-analysis of 10 cohort studies of buccal mucosa graft urethroplasty and end-to-end anastomosis in short segment bulbar urethral stricture reported a recurrence rate of 30% ( Yuri et al, 2016 ). The current survey, evaluated by an independent CRO, included complex penile and longer strictures ( Liu et al, 2016 , Ortega and Pena, 2009 , Bello, 2016 , Breyer et al, 2010 , Yalcinkaya et al, 2015 ), and excluded end-to end anastomosis (known to have a very high SR) ( Ortega and Pena, 2009 , Ivaz et al, 2017 ). One can therefore consider the results of our study in general accordance with buccal mucosa urethroplasty ( Yuri et al, 2016 , Chauhan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 10 cohort studies of buccal mucosa graft urethroplasty and end-to-end anastomosis in short segment bulbar urethral stricture reported a recurrence rate of 30% ( Yuri et al, 2016 ). The current survey, evaluated by an independent CRO, included complex penile and longer strictures ( Liu et al, 2016 , Ortega and Pena, 2009 , Bello, 2016 , Breyer et al, 2010 , Yalcinkaya et al, 2015 ), and excluded end-to end anastomosis (known to have a very high SR) ( Ortega and Pena, 2009 , Ivaz et al, 2017 ). One can therefore consider the results of our study in general accordance with buccal mucosa urethroplasty ( Yuri et al, 2016 , Chauhan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] in their study in 40 patients with anterior urethral stricture treated with dorsal onlay BMG urethroplasty suggested that stricture length and localization are the most important variables for desirable success and also reported 82% success rate for patients with stricture length >4 cm and 76% for stricture length ≥6 cm. According to Yalcinkaya et al .,[ 2 ] length of stricture dramatically and statistically affects the outcomes of urethroplasty, and using BMG, they also reported 88% success rate for stricture length ≤7 cm and only 40% success rate for stricture length >7 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucosa graft (OMG) is the graft of choice for all urethral substitutions and has been considered as the gold standard graft. Recently, concerns have been raised about the factors responsible for poorer outcomes after buccal graft anterior urethroplasty which include long-segment urethral strictures[ 1 2 ] and tobacco-exposed oral mucosa. [ 3 ] There is thus a need to search for alternate grafts for substitution in such scenario.…”
Section: Introductionmentioning
confidence: 99%
“…OMGs have poorer overall success rates and inconsistent results in long anterior urethral strictures. Success rates of OMG urethroplasty in strictures of >7 cm is almost half that of those <7 cm (40% vs 88%) [3] . Chauhan et al [5] compared the success of BMG with a lingual mucosal graft in long urethral stricture patients (range 3.2–13.4 cm) and found the stricture length was the significant predictor of success and success was higher in shorter strictures on univariate analysis.…”
Section: Introductionmentioning
confidence: 93%
“…OMGs have continued to give reliable and reproducible results in past two decades and have virtually become the ‘one-stop shop’ for all urethral reconstructive needs. However, recent literature has highlighted some concerns in the use of OMG in certain subsets of patients, namely those with tobacco-exposed oral mucosa [2] and those with pan-anterior strictures [3] that necessitate looking beyond the oral mucosa.…”
Section: Introductionmentioning
confidence: 99%